2015
DOI: 10.1002/pd.4674
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive genetic counseling challenges associated with diagnostic exome sequencing in a large academic private reproductive genetic counseling practice

Abstract: Despite having experienced complexity and identified challenges of the reproductive genetic counseling, availability of diagnostic WES contributed important information that aided in prenatal care planning and decision-making. Future enhanced provider education and larger studies to systematically study the integration of WES in reproductive genetic counseling and prenatal care will be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 20 publications
0
64
0
1
Order By: Relevance
“…These guidelines incorporate five categories of variant classification: benign, likely benign, uncertain (variants of uncertain significance (VUS)), likely pathogenic, and pathogenic. 10 An uncertain finding can be frustrating for clinicians and patients, 11 but it is a necessary result when there is insufficient information to determine whether a variant is benign or pathogenic. Reports with uncertain findings can result in additional medical costs and a continued diagnostic odyssey when a provider lacks sufficient information to rule in or rule out a diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines incorporate five categories of variant classification: benign, likely benign, uncertain (variants of uncertain significance (VUS)), likely pathogenic, and pathogenic. 10 An uncertain finding can be frustrating for clinicians and patients, 11 but it is a necessary result when there is insufficient information to determine whether a variant is benign or pathogenic. Reports with uncertain findings can result in additional medical costs and a continued diagnostic odyssey when a provider lacks sufficient information to rule in or rule out a diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the clinical utility of DES for prenatal and neonatal patients due to increasing ease of DES and knowledge of the human genome [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, Alamillo et al reported relevant mutations in four of seven prenatal cases 135 , and Drury et al found a 25% total detection rate in 24 fetuses with abnormal ultrasound findings, including a definitive diagnosis in five and plausible diagnosis in one 11 . Our early results also indicate that the detection rate of a significant genetic abnormality with prenatal exome sequencing for fetuses with single or multiple congenital anomalies is at least 30% 18, 128 .…”
Section: Prenatal Whole-exome Sequencing Will Change Our Ability To Imentioning
confidence: 57%
“…Healthcare providers must consider the consequences of their rapid introduction into the clinic because of the still-limited knowledge about the test performance of some assays in routine clinical practice, concerns related to cost-conscious implementation of optimized screening and testing strategies, equal access, and appropriate selection of who will benefit most. The ever-increasing amount of genetic information that can be obtained preconceptionally and prenatally also brings about ethical and genetic counseling challenges 9, 1821 .…”
Section: Introductionmentioning
confidence: 99%